â€œScan & Payâ€ : Developing a Conceptual Model on â€œIntention to Adoptâ€ UPI Payment Apps by the Unorganized Retail Sector Using the Extended Valence Theory (EVT) - Giri, Arunangshu; Biswas, Wendrila (Indian Journal of Finance, 2025)
Purpose : Despite the governmentâ€™s efforts to endorse a cashless economy, the adoption rate of digital payment methods, such as unified payment interfaces (UPI), remained low in the unorganized Indian retail sector. This research paper investigated positive and negative factors that impacted the intention to adopt UPI payment apps by unorganized retailers. It also developed a conceptual model to explain the adoption intention of UPI payment apps with the help of extended valence theory (EVT). Design/Methodology/Approach : A qualitative study was conducted using NVIVO-15 software to develop a conceptual model based on EVT. Forty-five semi-structured, in-depth interviews with unorganized retailers were executed using the snowball sampling technique. Findings : A conceptual model was developed to analyze the factors influencing the adoption intention of UPI payment apps. The study identified several positive and negative valences, along with the trust factor, that affected adoption intention. This model suggested that positive valences were perceived usefulness, perceived ease of use, social influence, and facilitating conditions, while negative valences were perceived financial risk, perceived security risk, and perceived operational risk. Implications : This study contributed to the theoretical understanding of unorganized retailersâ€™ adoption intention of UPI payment apps using EVT. It also suggested managerial implications for policymakers as well as financial institutions to play an active role in penetrating the retail market of the unorganized sector in India. Originality/Value : The present short communication study is unique, as positive and negative valences, as complementary predictors of adoption intention of UPI payment apps in the unorganized retail sector have not been explored in the Indian context.